FORMATION OF SHRINKAGE POROSITY DURING SOLIDING OF STEEL - Sh. B.Tashbulatov; M. N. Gaybullaev; I.T. Tukhtaboev; I.S. Abdukahorov; B.N. Turajonov (Scholars Digest Publishing, 2024)
In this article, the formation of abrasion pores during the transition of metals from a liquid state to a solid state, and the effect of their formation on the quality of the casting is studied. Shrinkage pores, when the metal goes into a liquid state, there are several analyzes of the formation of shrinkage pores due to the fact that the volume of the metal in the liquid state is larger than the volume of the metal in the solid state, and it shrinks again during the cooling process.
Keywords: steel, alloy, porosity, liquid metal, furnace, liquation, shrinkage, ProCAST program.